Relasi Kuasa dan Islamisasi : Dinamika Hukum Islam di Kesultanan Samudera Pasai - Maghfirah, Moona Maghfirah (PERADA, 2024)
This article examines Islamic Sultanates in Sumatra with a focus on the Sultanate of Samudra Pasai, one of the most influential kingdoms in the development of Islam in the archipelago. Sociohistorically, the Sultanate of Samudra Pasai not only functioned as a center of political power and authority, but also played an important role in various dimensions of life-political, economic, cultural, and religious. Its location in the western region of Sumatra, as the starting point of Islam's entry into the archipelago, made Samudra Pasai an important center in the history of Islam in Indonesia. This study highlights the complexity of law implementation in Samudra Pasai, where there was an overlap between Islamic law and customary law. Through a historical literature study approach and the application of Michel Foucault's power relations theory, the author reveals that the Islamization process in Samudra Pasai was laden with power dynamics. The findings show that Islamic laws implemented by the sultanate were often intervened by sultanate authorities for the sake of the ruler's political and social interests. This analysis highlights how power influenced and shaped the application of Islamic law in the Sultanate of Samudra Pasai, providing insight into the interaction between law, power and religion in the context of Indonesian history.